Analysis of radionuclide concentration in air released through the stack of a radiopharmaceutical production facility based on a medical cyclotron. (November 2015) - Giardina, M.; Tomarchio, E.; Greco, D.
Abstract: Positron emitting radionuclides are increasingly used in medical diagnostics and the number of radiopharmaceutical production facilities have been estimated to be growing worldwide. During the process of production and/or patient administration of radiopharmaceuticals, an amount of these radionuclides might become airborne and escape into the environment. Therefore, the analysis of radionuclide concentration in the air released to the stack is a very important issue to evaluate the dose to the population living around the plant. To this end, sampling and measurement of radionuclide concentration in air released through the stack of a Nuclear Medicine Center (NMC), provided with a cyclotron for radiopharmaceuticals production, must be routinely carried out with an automatic measurement system. In this work is presented the air monitoring system realized at "San Gaetano" NMC at Bagheria (Italy) besides the analysis of the recorded stack relesead air concentration data. Sampling of air was carried out continuously and gamma-ray spectrometric measurement are made on-line and for a short time by using a shielded Marinelli beaker filled with sampled air and a gamma detector. The use of this system allows to have 1440 values of air concentration per day from 2002, year of the start of operation with the cyclotron. Therefore, the concentration values are very many and an analysis software is needed to determine the dose to the population. A comparison with the results of a simulation code based on a Gaussian Plume air dispersion modelling allow us to confirm the no-radiological significance of the stack effluent releases in terms of dose to population and to evaluate possible improvements in the plant devices to reduce the air concentration at stack. Highlights: Monitoring of air released through the stack of a Nuclear Medicine Center. Identification of main contamination sources and operative procedures optimization. Improvements in the protection devices to reduce the air concentration at stack. Analysis of concentration data to evaluate dose to population living near the plant.